DETERMINAN KEPUASAN BELANJA KONSUMEN SAYUR ONLINE - James Sakoikoi; Sony Heru Priyanto (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2019)
This study aims to: find determinants of vegetable consumer satisfaction (online) including trust, product appearance (product packaging), product quality, website quality, information content, product diversity, and ease of transaction. The research was conducted in April 2018 until June 2018, for approximately 60 days. Whereas the research site is in the Salatiga area of ??Central Java, Semarang Regency. This research is a kind of quantitative descriptive research and the method used in this study is the survey method. The sampling technique used in sampling is non probality sampling by accidential sampling. Quantitative descriptive data analysis with simple linear regression analysis. The results of the analysis show that the product appearance variable (product packaging), product quality, website quality, information content, diversity and ease of transactions are very influential or significant towards satisfaction, while the trust variable does not affect satisfaction, because there are factors that influence satisfaction, namely crosstab results the value has the same is not high and not low, so that the population collects or does not spread and there is a fairly high multicollinearity.